2020
DOI: 10.1101/2020.05.25.115360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glutamate transporters contain a conserved chloride channel with two hydrophobic gates

Abstract: Glutamate is the most abundant excitatory neurotransmitter in the central nervous system, therefore its precise control is vital for maintaining normal brain function and preventing excitotoxicity 1 . Removal of extracellular glutamate is achieved by plasma membrane-bound transporters, which couple glutamate transport to sodium, potassium and pH gradients using an elevator mechanism 2-5 . Glutamate transporters also conduct chloride ions via a channel-like process that is thermodynamically uncoupled from trans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…In addition, these transporters mediate a glutamate-dependent anion flux, which under physiological conditions is carried by Cl – ions ( Picaud et al, 1995 ; Wadiche et al, 1995b ; Eliasof and Jahr, 1996 ). The chloride channel forms at the interface of the transport and scaffold domains during the transport cycle ( Ryan et al, 2004 ; Cater et al, 2014 , 2016 ; Cheng et al, 2017 ; Kolen et al, 2020 ; Chen et al, 2021 ) and the direction of this flux is determined by the driving force for chloride (i.e., the difference between membrane potential and reversal potential for chloride). The function of the chloride current remains incompletely understood but it has been suggested that it might serve to counterbalance the influx of positive charges due to glutamate transport and prevent cell depolarization ( Grewer and Rauen, 2005 ).…”
Section: Glutamate Transportersmentioning
confidence: 99%
“…In addition, these transporters mediate a glutamate-dependent anion flux, which under physiological conditions is carried by Cl – ions ( Picaud et al, 1995 ; Wadiche et al, 1995b ; Eliasof and Jahr, 1996 ). The chloride channel forms at the interface of the transport and scaffold domains during the transport cycle ( Ryan et al, 2004 ; Cater et al, 2014 , 2016 ; Cheng et al, 2017 ; Kolen et al, 2020 ; Chen et al, 2021 ) and the direction of this flux is determined by the driving force for chloride (i.e., the difference between membrane potential and reversal potential for chloride). The function of the chloride current remains incompletely understood but it has been suggested that it might serve to counterbalance the influx of positive charges due to glutamate transport and prevent cell depolarization ( Grewer and Rauen, 2005 ).…”
Section: Glutamate Transportersmentioning
confidence: 99%
“…3d). We term this state "intermediate state" in the remainder of the manuscript, but cannot determine whether this state corresponds to an intermediate state previously observed structurally or computationally 23,[44][45][46][47] . As expected, the state-assignment algorithm mainly assigned three states in traces with elevated SNR > 2.…”
Section: Hs-afm-ls Detects Fast Transitions and An Intermediate Statementioning
confidence: 99%
“…Our knowledge of the structure of eukaryotic glutamate transporters is largely based on the crystal structure of the outward-facing [16], inward-facing [17], open states [18], Na + :substrate binding [19] and trimer assembly [20] of Glt Ph , a glutamate transporter homolog from the prokaryote Pyrococcus horikoshii. Glt Ph has ∼ 37% (high) aminoacid identity with human GLT-1.…”
Section: Table Of Contents Image Introductionmentioning
confidence: 99%
“…The general consensus is that all glutamate transporters assemble as trimers, with each monomer functioning independently from the others [20]. The trimeric assembly delimits a bowl-shaped concave aqueous basin that prevents glutamate molecules unbinding from the transporters from being lost to extracellular diffusion [21] and contains molecular determinants that are involved in Cl − channel activation of Glt Ph [18].…”
Section: Table Of Contents Image Introductionmentioning
confidence: 99%